A contribuição da psicologia no estudo da relação trabalho bancário-saúde - Ribeiro, Ana Maria de Melo [UNESP] (2006)
Countless transformations occurred in the world of work, resulting of the productive restructuration, had affected in a particular way the bank working atmosphere, with reflects on the health of these professionals. These new ways of organizations and managements, developing work atmospheres marked by overload and insecurity caused by aspects related to creativity and work satisfaction, resulted in changes on the identity and on the way of work of these professionals, which effects had been felt particularly on the process between health and illness on the work relations. From these considerations, this dissertation had as objective study the relation between banking work and health, by a research and an analyze of the existing scientific academic production about this subject. Therefore, this a documental research that has used as an information bank 05 summaries of Doctorate Theories and 31 Master Dissertations which has this thematic as study objective. This material came from brazilian Master's Degree programs, produced in 11 different discipline areas, and 15 of these dissertations are from the psychology area. For the treatment of the data and its systematization for interpretation was used the Content Analyzes, which results shows up, in a first moment, the interests of the Science for this subject, confirming its relevance. On the other hand, the Summaries analyzes shows that the barely totality of the production refers to the changes occurred on the conditions of the banking work as responsible for any kind of mental or physical illness on these type of workers. Another significant aspect of the analyzes is the verification of the knowledge fragmentation construction tendency that, in the specific relation between Banking Work and Health, was constructed from countless perspectives and theoretical points, according to the area that had produced it. This data verify the importance of the search for interactivity process of this knowledge